Production, composition and quality of deferred corn (Semiárida, 2020)
The dry matter (DM) yield and plant composition of deferred cultivated com was studied near the city of V. Mercedes (San Luis Province; 33° 39' S, 65° 22' 0, and 505 m in altitude). A randomized complete block design with 4 replications was used. Three commercial cultivars in plots of 20.5 m2 were evaluated. Samples were taken when alter the grain became pasty and hard. Dry matter yield of the whole plant and its components (Ieaf, stem, and spike) was determined. Means were compared by analysis of variance using Duncan's Multiple Range Test (P
Keywords: deferred corn; cultivar; production; in sacco degradability.